2007
DOI: 10.1128/jb.00791-07
|View full text |Cite
|
Sign up to set email alerts
|

The Alcohol Dehydrogenase Gene adhA in Corynebacterium glutamicum Is Subject to Carbon Catabolite Repression

Abstract: Corynebacterium glutamicum has recently been shown to grow on ethanol as a carbon and energy source and to possess high alcohol dehydrogenase (ADH) activity when growing on this substrate and low ADH activity when growing on ethanol plus glucose or glucose alone. Here we identify the C. glutamicum ADH gene (adhA), analyze its transcriptional organization, and investigate the relevance of the transcriptional regulators of acetate metabolism RamA and RamB for adhA expression. Sequence analysis of adhA predicts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
87
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 53 publications
2
87
0
Order By: Relevance
“…The regulation of C. glutamicum metabolism in the presence of various carbon sources clearly differs from that of E. coli or B. subtilis (Gerstmeir et al, 2003;Hayashi et al, 2002;Letek et al, 2006;Muffler et al, 2002). No direct evidence has been found of a CCR system in C. glutamicum (Bruckner & Titgemeyer, 2002;Gerstmeir et al, 2003;Han et al, 2007), although a CCR-like phenomenon has been reported from cells grown on medium containing glucose with either glutamate (Gerstmeir et al, 2003;Kramer et al, 1990;Kronemeyer et al, 1995) or ethanol (Arndt & Eikmanns, 2007;Kotrbova-Kozak et al, 2007). However, mechanisms of true induction and repression in the TCA cycle have not been studied in depth.…”
Section: Introductionmentioning
confidence: 91%
“…The regulation of C. glutamicum metabolism in the presence of various carbon sources clearly differs from that of E. coli or B. subtilis (Gerstmeir et al, 2003;Hayashi et al, 2002;Letek et al, 2006;Muffler et al, 2002). No direct evidence has been found of a CCR system in C. glutamicum (Bruckner & Titgemeyer, 2002;Gerstmeir et al, 2003;Han et al, 2007), although a CCR-like phenomenon has been reported from cells grown on medium containing glucose with either glutamate (Gerstmeir et al, 2003;Kramer et al, 1990;Kronemeyer et al, 1995) or ethanol (Arndt & Eikmanns, 2007;Kotrbova-Kozak et al, 2007). However, mechanisms of true induction and repression in the TCA cycle have not been studied in depth.…”
Section: Introductionmentioning
confidence: 91%
“…Besides, no HPr kinase/phosphatase system is found in the C. glutamicum genome. These differences in the molecular characteristics are likely reflected in the capacity of C. glutamicum to cometabolize glucose and a variety of carbon sources, including sugars, organic acids, and aromatic compounds without catabolite repression (17)(18)(19)(20)(21)(22)(23)(24), expect for a few cases (25)(26)(27).…”
mentioning
confidence: 99%
“…The organism can use a variety of sugars (e.g., glucose, fructose, sucrose, ribose, or maltose) and organic acids (acetate, propionate, pyruvate, lactate, or citrate) as single or combined carbon and energy sources for growth and also for amino acid production. C. glutamicum is also able to use ethanol as a sole carbon and energy source, using alcohol dehydrogenase (ADH) and acetaldehyde dehydrogenase (ALDH) for NAD-dependent oxidations to acetate, which is then activated to acetyl coenzyme A (acetyl-CoA) and channeled into the citric acid and glyoxylate cycles (2,4,5,44). The ADH gene (adhA) of C. glutamicum has been shown to be subject to complex, carbon source-dependent regulation by the global transcriptional regulators RamA, RamB, and GlxR (2,6,43).…”
mentioning
confidence: 99%